Effect of Consumer-Brand Relationships to Purchase Intention: A cross-cultural research from Nordic automotive market - Mäki, Aino (My University, 2018)
Purpose – This research explores the relationship between consumer-brand relationship and car purchase-intention in three Nordic countries; Finland, Sweden and Denmark, from the perspective of automotive manufacturer Nissan. The research questions of the study are Does consumerbrand relationship impact on car purchase intention in Nordics? and Does Nordic culture have an impact on consumer-brand relationship or purchase intention of a Nissan? Definitions – Consumer-brand relationships explain the relationship consumer has with the components of brand (brand equity, brand engagement, brand related associations, brand image, and the different levels of brand knowledge). Brand is viewed as something consumers attach feelings to, form relationships with and which forms in consumers’ minds. Purchase intention forms of brand consideration and brand preference. Research approach – This research is quantitative by its nature and follows a deductive approach. Data was collected through online questionnaire and analyzed via SPSS Statistics computer program. A sample of 1,500 respondents that met the following preset restrictions was collected; age of 18 to 64 years old, owns a driver’s license, had an intention to purchase a car within next three years. Findings – Findings of this research suggest that consumer-brand relationship and its components have a clear, non-deniable relationship to purchase intention. Brand familiarity, positive brand opinion along with aided and spontaneous brand awareness effect brand consideration and brand preference of Nordic consumer. In addition to that, Nordic culture, in particular, was not found to have an effect on consumer-brand relationships or car purchase intention. Contributions – This research contributes to existing literature by offering cross-country comparisons from automotive industry, along with in-depth definitions of brand components. The research proves the relation between consumer-brand relationship and purchase intention. Managerial implications of this research suggest that brand should be viewed as combination of all of its components, instead of a single unit and the focus on marketing communications should shift to spontaneous brand awareness from traditional brand familiarity view.
Keywords: Consumer-brand relationship; purchase intention; international branding; automotive industry; Nordic culture; fi=Markkinointi|en=Marketing|; fi=Master's Degree Programme in International Business|